KEBIJAKAN PENGEMBANGAN OBYEK DAYA TARIK WISATA - Fitriani, Aida (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
The development of tourist attraction objects must be supported by a strong commitment to make it happen. Accessibility and transportation networks are still limited, marketing and promotions are not yet optimal, limited human resources and inadequate budgets are certainly obstacles. Other aspects relate to institutions (apparatus' understanding of the concept and definition of tourist areas as well as coordination between related agencies), policies and regulations for managing tourist areas (local, regional, national and international levels) and human resources for managers and participation of local residents in area management. tourism, the condition of facilities and infrastructure, and the condition of the tourist objects that will be developed are also significant factors